2018
DOI: 10.1021/acs.chemmater.8b01134
|View full text |Cite
|
Sign up to set email alerts
|

Cation Exchange-Mediated Synthesis of Library of Plasmomagnetic Nanoheterostructures: Transformation of 2-Dimensional-Shaped Fe7S8 Nanoplates to Cu–Fe–S-Based Ternary Compound

Abstract: Cation exchange mediated synthesis of nanoheterostructures (NHSs), core–shell structure or segmented nanostructures are gaining high interest in nanoscience research as the process gives a wide window of opportunity to tune and enhance the photophysical properties of semiconductors. Presence of point defects or layered structure of the material accelerates cation exchange process, which is well established for copper chalcogenide system. Here, we are reporting facile synthesis of high-quality Fe7S8 hexagonal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Since ion exchange leads to hollowing or tunneling of solid precursor wires, rods, and spheres without destroying the morphologies and structures [12], the original stability of MSs may be retained in the cation exchange-generated MSs. In general, the cation exchange preparation of MSs is governed by lattice structure stability [70] and defects in the crystal structure [71,72] of the precursor sulfide.…”
Section: Cation Exchangementioning
confidence: 99%
“…Since ion exchange leads to hollowing or tunneling of solid precursor wires, rods, and spheres without destroying the morphologies and structures [12], the original stability of MSs may be retained in the cation exchange-generated MSs. In general, the cation exchange preparation of MSs is governed by lattice structure stability [70] and defects in the crystal structure [71,72] of the precursor sulfide.…”
Section: Cation Exchangementioning
confidence: 99%
“…Moreover, CE has been employed as an effective tool for the synthesis of NHSs, and till now, there are several reports on different cations, like Cu + , 23 Cd 2+ , 24 Pb 2+ , 25 Hg 2+ , 26 and Ag + , 27 which have been used for this kind of reaction to occur. Copper cation exchange is widely studied as it is a fruitful way to fabricate copper-based systems; among which, many of these are emerging as an important plasmonic materials, for example, Cu 3 SbSe 3 , 28 Cu 5 FeS 4 , 29 Cu 3 BiS 3 , 30 CuInS 2 , 31 CuInSe 2 , 32 and so forth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Moreover, CE has been employed as an effective tool for the synthesis of NHSs, and till now, there are several reports on different cations, like Cu + , Cd 2+ , Pb 2+ , Hg 2+ , and Ag + , which have been used for this kind of reaction to occur. Copper cation exchange is widely studied as it is a fruitful way to fabricate copper-based systems; among which, many of these are emerging as an important plasmonic materials, for example, Cu 3 SbSe 3 , Cu 5 FeS 4 , Cu 3 BiS 3 , CuInS 2 , CuInSe 2 , and so forth. Although there is a huge research activity on the copper-based cation exchange reaction, fewer reports have been found on Ag + cation-exchanged heterostructure formation where Ag + ion plays a key role in cation exchange transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrrhotite (Fe 7 S 8 ) is one of the many stoichiometric forms of iron sulfide and is an attractive candidate for electrocatalytic applications and used as an anode material for lithium–sodium ion batteries. Despite its potential, this material has not been investigated much. Only a few attempts have been made where Fe 7 S 8 was laminated, doped, and partially and completely cation-exchanged with another material to attain a hybrid heterogeneous structure, but even this study still lacked a systematic synthesis approach. In the last decade, multiple noble metal-iron oxide based hybrid heterodimers and trimers have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Despite its potential, this material has not been investigated much. Only few attempts have been made where Fe7S8 was laminated, 19 doped, 21 partially and completely cation exchanged 22 with another material to attain hybrid heterogeneous structure but even this study still lacked a systematic synthesis approach. Since last decade, multiple noble metal-iron oxide based hybrid heterodimers and trimers have been reported.…”
mentioning
confidence: 99%